Peningkatan Kapasitas Lembaga Pendidikan Anak Usia Dini POS PAUD Ar-Raudhoh Kecamatan Gondang Wetan Pasuruan - Mishbahuddin, Mohamad (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Child education age early Already duly become attention full by all party Good government nor parents _ as a madrasah ula for their children, there a number of community knowledge _ need know with quick that is it worked participant educate fulfill 9 years must learning is based on success learning at age early, start from awareness public related development participant educate as well as factor What just what is necessary the relevant level with age them, as well cooperation party government, in matter This government village related awareness the people school his son realized early, then activity devotion This aims (1) realization enhancement quality education, efforts are necessary done educators and staff education oriented to enhancement qualifications, (2) existence an appropriate learning strategy _ For applied in the learning process, (3) Unpacking the old way (opens mindsite) think education with prioritize draft collaboration (partnership), the method used is studies case with the core instrument is interview, As for the results from activity This growth awareness will the importance of age education early from parents _ up to government village